The Carbon Conundrum: Exploring CO2 Emissions, Public Debt, and Environmental Policy - Mohd Shahidan Shaari; Amri Sulong; Miguel Angel Esquivias; Evan Lau; Abdul Rahim Ridzuan (Emerging Science Journal, 2024)
This study addresses a critical gap in the literature by examining the impact of CO2emissions on public debt in Malaysia, employing a non-linear autoregressive distributed lag (ARDL) approach spanning from 1980 to 2020. This methodology captures the non-linear relationship between CO2 emissions and public debt, providing nuanced insights into how environmental factors shape fiscal dynamics. Despite encountering challenges arising from the limited body of literature on this specific relationship, the study highlights key findings with profound implications for policymakers. The inverse correlation between trade openness and public debt underscores the influence of international trade on Malaysia's fiscal landscape, while a positive association between investment and public debt emphasizes the importance of prudent debt management for economic growth. Furthermore, the negative relationship between higher foreign direct investment and long-term public debt highlights the need to foster an investor-friendly environment. A pivotal contribution is the confirmation of a positive link between CO2 emissions and public debt, urging policymakers to prioritize emission reduction strategies, implement carbon pricing, and promote green technologies. This research offers a comprehensive understanding of the intricate interplay between CO2emissions and public debt, providing valuable insights for informed policy decisions in the Malaysian context. Doi: 10.28991/ESJ-2024-08-03-08 Full Text: PDF